´Dealing with diversity´: debating the focus of teacher education for inclusion. Issue 1 (1st January 2020) - Guðjónsdóttir, Hafdís; Óskarsdóttir, Edda
ABSTRACT: Increasingly across the world, teachers are working with diverse groups of learners in inclusive school settings, as inclusion is seen as a strategy to promote social cohesion, citizenship and a more equitable society. Countries working towards this vision need to emphasise more effective teacher education programmes and systems that focus on enabling teachers to engage in inclusive practice in order to provide high-quality education for all learners.